2021
DOI: 10.3389/fimmu.2021.785549
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Circulating Follicular T Helper Cells and Regulatory B Cells in Children With Extrinsic Atopic Dermatitis

Abstract: Atopic dermatitis (AD) in early childhood is often the initial manifestation of allergic disease associated with high IgE. Accumulating evidences show that follicular helper T (Tfh) cells play a critical role in promoting B cell differentiation and IgE production, human regulatory B (Breg) cells participate in immunomodulatory processes and inhibition of allergic inflammation. However, the roles and interactions between IL-10-producing Breg cells and Tfh cells in childhood AD are unclear. In this study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The authors concluded that an impairment in Breg cells may be responsible for TFH-dependent humoral response in SLE. Similar findings were reported before, strengthening the conclusion of the authors [ [18] , [19] , [20] ]. Last but not least, stress has long been believed to play a critical role in initiation and exacerbation of the autoimmune disorders [ 21 ].…”
Section: Basic Components Of Autoimmunity During Auto13supporting
confidence: 92%
“…The authors concluded that an impairment in Breg cells may be responsible for TFH-dependent humoral response in SLE. Similar findings were reported before, strengthening the conclusion of the authors [ [18] , [19] , [20] ]. Last but not least, stress has long been believed to play a critical role in initiation and exacerbation of the autoimmune disorders [ 21 ].…”
Section: Basic Components Of Autoimmunity During Auto13supporting
confidence: 92%
“…Increasing evidence suggests that follicular helper T cells (Tfh) are crucial in promoting IgE production. In this study, the immunoinfiltration analysis showed a significant increase in Tfh (Jiang et al, 2021). Natural killer cells (NK) are associated with the pathophysiology of AD, and immune cell analysis demonstrated that NK cells and T cell subpopulations are associated with the severity of AD(Worm et al, 2023).…”
Section: Discussionsupporting
confidence: 54%
“…In our study, Tfh cells, a subset of CD4 + T cells, were enriched in AD patients over controls. A negative relationship between IL-10 + Breg cells and Tfh cell differentiation in children with extrinsic AD has been observed ( 57 ), which may promote researchers focusing on the function of Tfh cells. Interestingly, there was a close relationship between the above-mentioned immune cells and the hub MitoDEGs, which promoted our understanding of the interaction among mitochondria and innate immune cells in the EIME of AD patients.…”
Section: Discussionmentioning
confidence: 99%